THE ROLE OF MODERN TOOLS IN EDUCATION (Web of Teachers: Inderscience Research, 2025)
The modern education system is constantly being updated and developed. Today, the use of modern tools, technologies and methods in the educational process helps to make the learning process of students more effective and interesting. When talking about the role of modern tools in education, first of all, it is necessary to consider the importance of these tools in the educational process, their impact and how they benefit students.